The effects of competition on banks' risk taking with and without deposit insurance - Juha-Pekka Niinimäki (Bank of Finland, 2000)
We consider the joint effect of competition and deposit insurance on risk taking by banks when the riskiness of banks is unobservable to depositors.It turns out that the magnitude of risk taking depends on the type of bank competition.If the bank is a monopoly or banks compete only in the loan market, deposit insurance has no effect on risk taking.In that case the banks are too risky but extreme risk taking is avoided.In contrast, introducing deposit insurance increases risk taking if banks compete for deposits. Then, deposit rates become excessively high and force the banks to take extreme risks.Regarding the effects of increasing competition when there is deposit insurance, the results imply that deposit competition encourages risk taking but loan market competition does not.Our results can be extended more generally to insurance guaranty funds.
URN:NBN:fi:bof-20140807248
Keywords: 330; Deposit insurance; Insurance guaranty funds; Bank and insurance regulation; Moral hazard; Credit rationing; Financial Fragility